Seroprevalence of rubella in pregnant women - Tripathy, Sumeet R.; Menon, Aruna; Bhardwaj, Bikram; Namaji, Mohammed Ashraf Ali S.; Khardenavis, Nilesh A.; Gupta, Neha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Rubella is a droplet infection characterized by self-limiting illness. However infection during pregnancy may result in miscarriage, congenital birth defects leading to long term morbidity. The aim of the study was to estimate the seroprevalence of rubella immunity in pregnant women. Methods: Antenatal patients, irrespective of period of gestation, fulfilling the inclusion criteria were tested for rubella IgG antibodies. Results: A total of 258 pregnant women were included in the study. The estimated seroprevalence of immunity against Rubella infection was 70.5% (n=182) whereas 29.5% (n=76) were seronegative and thus susceptible to rubella infection. The distribution of seroprevalence of rubella immunity based on age group and gravidity were also evaluated. Conclusions: The results reveal high level of rubella sero positivity, which indicates continued transmission of rubella infection in the community.